A comparison of owner/operator and worker perspectives on workplace safety in the West Virginia logging industry. Issue 4 (1st February 2021) - Lundstrom, Eric W.; Myers, Douglas J.; Lundstrom, Wayne J.; Rauscher, Kimberly J.; Fullen, Mark
Abstract: Background: The logging industry is known to have one of the highest rates of fatal and nonfatal occupational injuries in the United States. Perspectives on why this study is so hazardous may differ between logging company owners/operators and workers. In this study, we explored and compared the safety perspectives of logging company owners/operators and workers in West Virginia. Methods: Using a mixed‐methods approach, we analyzed survey ( n  = 245) and interview ( n  = 14) data collected in 2015 from logging company owners/operators and workers in West Virginia. Survey data were analyzed via logistic regression; interview data were analyzed using thematic analysis. Response patterns were contrasted by occupational status (owners/operators vs. workers) in both analyses. Results: Owners/operators and workers agreed on several aspects of workplace safety including the importance of personal protective equipment and the benefits of mechanization when timber harvesting. Key differences observed between owners/operators and workers included why injuries are underreported and the effects of production pressures on safety. Conclusion: While there was much agreement, owners/operators and workers in the West Virginia logging industry reported differences in key domains of workplace safety. These differences should be taken into account when designing and implementing safety programs in the logging industry.